Unpacking the role of school climate factors in fostering teacher enjoyment and self-efficacy in higher education - Xiaoyi Bing; Jianqiao Cai (PLoS ONE, 2025)
The enjoyment and self-efficacy of teachers warrant significant attention, particularly given the global prevalence of high attrition and turnover rates in the profession. This study investigates the interrelationships among school climate factors, teacher self-efficacy, and enjoyment in higher education settings. Specifically, it aims to (a) examine how teachers perceived school environment factors influence their self-efficacy and enjoyment and (b) determine whether teachers’ self-efficacy mediates the effect of perceived school climate factors on teacher enjoyment. In so doing, three instruments including Perceived School Climate Scale (R-SLEQ), Teacher Self-Efficacy Scale (TSES), and Teacher Enjoyment Scale (TES) were used. Employing snowball sampling, we recruited 791 college teachers from 24 provinces in China. Structural equation modeling revealed that specific school climate factors significantly contribute to both teachers’ enjoyment and self-efficacy. Notably, colleague collaboration, resource availability, participative decision-making, and instructional innovation demonstrated direct positive effects on teacher enjoyment. Instructional innovation and colleague collaboration further exerted indirect effects on enjoyment through the mediation of self-efficacy. Finally, the practical implications of these findings for teacher education are discussed.